2019
DOI: 10.1123/ijspp.2018-0255
|View full text |Cite
|
Sign up to set email alerts
|

One-Repetition-Maximum Measures or Maximum Bar-Power Output: Which Is More Related to Sport Performance?

Abstract: The bar-power outputs were more strongly associated with sprint-speed and power performance than the 1RM measures. Therefore, coaches and researchers can use the bar-power approach for athlete testing and monitoring. Due to the strong correlations presented, it is possible to infer that meaningful variations in bar-power production may also represent substantial changes in actual sport performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 27 publications
14
37
0
Order By: Relevance
“…The rate of force development (RFD) is an important measurement in sports performance, as force application in many activities occurs over short time periods . Therefore, while peak force is a valid and highly reliable means of broadly monitoring neuromuscular function, rapid force production characteristics are equally valuable and more specific to the execution of explosive tasks . Unfortunately, only three training studies examining different contraction intents reported RFD variables .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of force development (RFD) is an important measurement in sports performance, as force application in many activities occurs over short time periods . Therefore, while peak force is a valid and highly reliable means of broadly monitoring neuromuscular function, rapid force production characteristics are equally valuable and more specific to the execution of explosive tasks . Unfortunately, only three training studies examining different contraction intents reported RFD variables .…”
Section: Discussionmentioning
confidence: 99%
“…14,100-102 Therefore, while peak force is a valid and highly reliable means of broadly monitoring neuromuscular function, rapid force production characteristics are equally valuable and more specific to the execution of explosive tasks. 2,[100][101][102][103] Unfortunately, only three training studies examining different contraction intents reported RFD variables. 43,47,48 Regardless, all three studies reported that isometric training with an "explosive" or "ballistic" intent was superior to ramping contractions for improving rapid force production.…”
Section: The Rate Of Force Developmentmentioning
confidence: 99%
“…Maximum bar-power output in the half-squat exercise Maximum mean propulsive power (MPP) output was assessed in the HS exercise on a Smith-machine (Hammer-Strength Equipment, Rosemont, IL, USA). Participants were instructed to execute three repetitions at maximal velocity for each load, starting at 40 % of their BM [19]. Participants executed a squat until the thigh was parallel to the ground and, after a command, moved the bar as fast as possible without their shoulders losing contact with the bar and without losing foot contact with the ground.…”
Section: Sprint Velocitymentioning
confidence: 99%
“…Participants executed a squat until the thigh was parallel to the ground and, after a command, moved the bar as fast as possible without their shoulders losing contact with the bar and without losing foot contact with the ground. A load of 10 % of BM was progressively added for each set until a decrement in the MPP was observed [19][20][21]. A 5-min rest period occurred between sets.…”
Section: Sprint Velocitymentioning
confidence: 99%
See 1 more Smart Citation